An Epidemiological Analysis of Hospitalizations for Migraine and Other Headache Syndromes Over the Last 15 Years in Brazil - Junior, Francisco Duque de Paiva Giudice; Melo, Leonardo José Rodrigues de Araújo; Aureliano, Kauane Emilly Ribeiro; Sousa, Bruno Henrique Alcântara Lopes de; Cavalcante, Francisco Luciano Honório Barreto; Sousa, João Marcelo Albuquerque Beserra de; Davi, Emanuela Freire Caetano; Rodrigues, Pedro Vitor Ferreira; Santos, Leonardo Elias Araujo dos; Tavares, Mariana Alcântara; Rosa, Rodrigo Fagundes da; Nogueira, Guilherme Nobre; et al. (Headache Medicine, 2023)
Full abstract in PDF.